2017
DOI: 10.1038/s41387-017-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month outcomes of a randomized trial of a moderate-carbohydrate versus very low-carbohydrate diet in overweight adults with type 2 diabetes mellitus or prediabetes

Abstract: Dietary treatment is important in management of type 2 diabetes or prediabetes, but uncertainty exists about the optimal diet. We randomized adults (n = 34) with glycated hemoglobin (HbA1c) > 6.0% and elevated body weight (BMI > 25) to a very low-carbohydrate ketogenic (LCK) diet (n = 16) or a moderate-carbohydrate, calorie-restricted, low-fat (MCCR) diet (n = 18). All participants were encouraged to be physically active, get sufficient sleep, and practice behavioral adherence strategies based on positive affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
223
2
28

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(260 citation statements)
references
References 20 publications
7
223
2
28
Order By: Relevance
“…The high‐protein prescriptions of the included studies ranged from 28% to 65% TEI or 1.2 to 2.0 g/kg IBW per day, and the moderate‐protein prescriptions ranged from 80 to 100 g/d or 0.8 to 1.2 g/kg IBW per day or were equivalent to 20% TEI. One study did not set a quantifiable protein prescription and could not be categorized but encouraged participants to consume their “usual protein intake” …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐protein prescriptions of the included studies ranged from 28% to 65% TEI or 1.2 to 2.0 g/kg IBW per day, and the moderate‐protein prescriptions ranged from 80 to 100 g/d or 0.8 to 1.2 g/kg IBW per day or were equivalent to 20% TEI. One study did not set a quantifiable protein prescription and could not be categorized but encouraged participants to consume their “usual protein intake” …”
Section: Resultsmentioning
confidence: 99%
“…It appears that no one single CHO amount for T2D is effective, yet there is growing interest in using more pronounced CHO restriction for at least part of the intervention duration. Very‐low‐CHO diet protocols (0‐50 g/d) tended to be described as ketogenic diets and/or set goals to achieve nutritional ketosis as measured by blood ketones . Proposed benefits of nutritional ketosis for T2D include decreased circulating glucose and insulin and increased ketone signalling, which may provide protection against oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…All 27 studies reported outcomes data for people with T2D and thus were appropriate for consideration in the development of nutritional recommendations for T2D management. Of the 10 RCTs, all of which reported on glycaemic control, nine found that a low‐carbohydrate diet resulted in a significant change from baseline to end of study; six also found a superior between‐group reduction favouring the low‐carbohydrate diet . While some studies found that the control diet also improved glycaemic control significantly from baseline, none found the control diet superior to the low‐carbohydrate diet.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 single‐arm and non‐randomized trials found that a low‐carbohydrate diet significantly improved glycaemic control from baseline to end of study; the two studies that made between‐group comparisons found the low‐carbohydrate diet superior to the control diet . We identified eight longer‐term studies (1‐3 years' duration), of which five found significant glycaemic benefit sustained with a low‐carbohydrate diet; these include two 2‐year trials and a 3‐year trial . Another longer trial also found sustained improvement in glycaemic control at 44 weeks .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation